Formulasi dan karakteristik fisikokimia banana bar pisang candi (Musa paradisiaca linn) dan tepung sorgum sebagai alternatif pangan low GI (indeks glikemik rendah) bagi penyandang obesitas - Randhiki Gusti Perdana; Muh. Agus Ferdian (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Obesity is a condition where there is excessive accumulation of fat in the body. As a result, weight is far above standard and can endanger health. People with obesity have a higher risk of developing the disease than people with normal nutritional status. An alternative in overcoming this is the intake of foods that have a low GI. It is necessary to develop low GI food types as an alternative to food or snacks that have a low glycemic index value, such as banana bars. The purpose of this study was to obtain the formulation and physicochemical characteristics of the Banana Bar temple banana (Musa paradisiaca Linn) and sorghum flour as an alternative to Low GI (Low Glycemic Index) food for obese people. The research consist of three stages, the first is formulation and manufacture of Banana Bars from candi banana, maizena and sorghum flour, the second is sensory and physicochemical characterization of Banana Bars, the third is Glycemic index analysis of Banana Bar products. The results showed that the most preferred banana bar was the 40% candi banana, 30% sorghum flour and coconut sugar. The physicochemical characteristics of Banana Bar products have a protein content of 4.09, 0.32 fat, 41.87 water content, 0.88 ash, 52.29 carbohydrates, and 0.56 crude fiber. While the glycemic index value of Banana Bar products is 72.95 (medium).